A Critical Discourse Analysis of Cultural Identity Representation, Algorithmic Culture, and Digital Commodification in Indonesian TikTok Content: A Fairclough Approach - Dewi Wulandari; Jumino Suhadi; Devi Pratiwy (Edulitics (Education, Literature, and Linguistics) Journal, 2026)
This study aims to examine how cultural identity is represented, negotiated, and commodified in Indonesian TikTok content within an algorithm-driven digital environment. TikTok has emerged as a dominant platform where cultural identity is constructed and circulated through short-form audiovisual content. While previous studies have explored cultural identity and digital discourse, limited research integrates these discussions with algorithmic culture and digital commodification, particularly in the Indonesian context. This study employs a qualitative descriptive approach using Norman Fairclough’s Critical Discourse Analysis (CDA) framework. A total of 30 TikTok videos were selected through purposive sampling from an initial dataset of 120 videos. The data include verbal expressions, captions, hashtags, visual elements, and audience comments, which were analyzed across textual, discursive, and social dimensions. The findings reveal that cultural identity on TikTok is constructed through recurring linguistic and visual patterns, including identity markers, local language expressions, and cultural symbols. At the discursive level, creators adapt cultural content to platform conventions, audience engagement, and visibility strategies, resulting in hybrid forms of representation. At the social level, cultural identity functions both as a marker of belonging and as a commodified digital resource within the attention economy. The study further demonstrates that authenticity, hybridization, and commodification operate as interconnected processes rather than separate categories, forming a continuum of cultural representation in digital environments. This study contributes to digital discourse and cultural identity research by integrating CDA with platform dynamics and providing empirical evidence from Indonesian TikTok content.